Pengembangan Instrumen Tes Daya Ledak Tendangan Dollyo Taekwondo Berbasis Teknologi - Jonas Solissa (LP. Ma'arif Janggan Magetan, 2023)
Kick power is an important parameter in taekwondo. Until now, there is no technology-based test instrument that can measure the explosive power of taekwondo kicks. The purpose of this study was to develop and validate a technology-based taekwondo kick explosive power test instrument. This research uses the type of research and development research. The research and development research procedure consists of the following steps: (1) needs analysis, (2) initial product, (3) expert evaluation, (4) product trial, (5) product revision, and (6) results the final product. This research was conducted on students of the Physical Education Study Program at Pattimura University, Ambon. The small group trial sample consisted of 60 male students. The large group trial sample consisted of 120 male students. The sample for instrument norms is 200 temple students and female students. Test product reliability using test-retest techniques. This study produced a test instrument for taekwondo kick explosive power: (1) valid with a validity coefficient of 0.874, (2) reliable with a reliability coefficient of 0.989 and (3) equipped with assessment norms for taekwondo kick explosive power classification.